Entropy in scalp EEG can be used as a preimplantation marker for VNS efficacy - Sklenarova, B; Chladek, J; Macek, M; Brazdil, M; Chrastina, J; Jurkova, T; Burilova, P; Plesinger, F; Zatloukalova, E; Dolezalova, I (Scientific reports, 2023)
Vagus nerve stimulation (VNS) is a therapeutic option in drug-resistant epilepsy. VNS leads to ≥ 50% seizure reduction in 50 to 60% of patients, termed "responders". The remaining 40 to 50% of patients, "non-responders", exhibit seizure reduction < 50%. Our work aims to differentiate between these two patient groups in preimplantation EEG analysis by employing several Entropy methods. We identified 59 drug-resistant epilepsy patients treated with VNS. We established their response to VNS in terms of responders and non-responders. A preimplantation EEG with eyes open/closed, photic stimulation, and hyperventilation was found for each patient. The EEG was segmented into eight time intervals within four standard frequency bands. In all, 32 EEG segments were obtained. Seven Entropy methods were calculated for all segments. Subsequently, VNS responders and non-responders were compared using individual Entropy methods. VNS responders and non-responders differed significantly in all Entropy methods except Approximate Entropy. Spectral Entropy revealed the highest number of EEG segments differentiating between responders and non-responders. The most useful frequency band distinguishing responders and non-responders was the alpha frequency, and the most helpful time interval was hyperventilation and rest 4 (the end of EEG recording).
Keywords: Seizures; Humans; Entropy; Vagus Nerve; nervus vagus; hyperventilace; Drug Resistant Epilepsy; záchvaty; výsledek terapie; Hyperventilation; lidé; elektroencefalografie; vagová stimulace; Scalp; refrakterní epilepsie; Treatment Outcome; skalp; Electroencephalography; Vagus Nerve Stimulation; entropie